Hubungan Kepatuhan Kunjungan Antenatal Care dengan Kejadian Anemia pada Ibu Hamil di Klinik Romana Desa Tanjung Anom, Kecamatan Pancur Batu, Kabupaten Deli Serdang - Lenny Sepriani Br Silalahi; Nurdiana Manurung (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background:Anemia in pregnancy remains a significant public health problem that adversely affects maternal and fetal health. Compliance with antenatal care (ANC) visits plays an essential role in the prevention and early detection of anemia. However, non-compliance with ANC visits is still frequently observed among pregnant women, increasing the risk of anemia. Objective:This study aimed to determine the relationship between compliance with antenatal care visits and the incidence of anemia among pregnant women at Romana Clinic, Tanjung Anom Village, Pancur Batu Subdistrict, Deli Serdang Regency. Methods:This study employed a quantitative analytical observational design with a cross-sectional approach. A total of 60 pregnant women attending antenatal services at Romana Clinic were included in the study. Data on ANC visit compliance were collected through structured interviews, while anemia status was obtained from medical records based on hemoglobin examination results. Data were analyzed using univariate and bivariate analyses with the chi-square test at a significance level of p < 0.05. Results:The results showed that 60.0% of pregnant women were compliant with antenatal care visits, while 40.0% were non-compliant. Anemia was found in 35.0% of respondents. Among women who were compliant with ANC visits, 19.4% experienced anemia, whereas 58.3% of non-compliant women were anemic. The chi-square test revealed a significant relationship between ANC visit compliance and anemia incidence (p = 0.003). Conclusion:There is a significant relationship between compliance with antenatal care visits and the incidence of anemia among pregnant women. Regular ANC visits play an important role in the prevention and early detection of anemia during pregnancy.